Improving Retail Operational Efficiency Through an Intuitive Web-Based Point of Sales Information System: A Case Study at Ternak Express - Rinaldy Hudan Permana; Dendy K Pramudito; Asep Arwan Sulaeman (Jurnal Informasi dan Teknologi, 2025)
The advancement of information technology has significantly impacted various sectors, including the fields of economics and business. One sector experiencing this transformation is livestock enterprises, such as Ternak Express, a business focused on providing animals as sacrificial (Qurban) and Aqiqah services. Currently, Ternak Express manages product and livestock data manually, a method that is prone to errors and can lead to data inconsistencies and potential financial losses for the business owner. To address this issue, this study aims to develop a web-based Point of Sale (POS) information system to support business operations more effectively and efficiently. The system is designed to manage sales transactions, product data, and customer information and generate business reports in a structured and automated manner. The development process uses the Laravel framework and applies the Waterfall model as the methodological approach. This research results in a web-accessible POS system that helps Ternak Express reduce data entry errors, streamline transaction processes, and improve the accuracy of business data management. With the implementation of this system, business operations are expected to become more integrated and professional, thereby supporting the company's growth and long-term development.